Antigen‐Specificity of T Cell Infiltrates in Biopsies With T Cell–Mediated Rejection and BK Polyomavirus Viremia: Analysis by Next Generation Sequencing - Zeng, G.; Huang, Y.; Huang, Y.; Lyu, Z.; Lesniak, D.; Randhawa, P. (American journal of transplantation, 2016)
This study interrogates the antigen‐specificity of inflammatory infiltrates in renal biopsies with BK polyomavirus (BKPyV) viremia (BKPyVM) with or without allograft nephropathy (BKPyVN). Peripheral blood mononuclear cells (PBMC) from five healthy HLA‐A0101 subjects were stimulated by peptides derived from the BKPYV proteome or polymorphic regions of HLA. Next generation sequencing of the T cell–receptor complementary DNA was performed on peptide‐stimulated PBMC and 23 biopsies with T cell–mediated rejection (TCMR) or BKPyVN. Biopsies from patients with BKPyVM or BKVPyVN contained 7.7732 times more alloreactive than virus‐reactive clones. Biopsies with TCMR also contained BKPyV‐specific clones, presumably a manifestation of heterologous immunity. The mean cumulative T cell clonal frequency was 0.1378 for alloreactive clones and 0.0375 for BKPyV‐reactive clones. Samples with BKPyVN and TCMR clustered separately in dendrograms of V‐family and J‐gene utilization patterns. Dendrograms also revealed that V‐gene, J‐gene, and D‐gene usage patterns were a function of HLA type. In conclusion, biopsies with BKPyVN contain abundant allospecific clones that exceed the number of virus‐reactive clones. The T cell component of tissue injury in viral nephropathy appears to be mediated primarily by an “innocent bystander” mechanism in which the principal element is secondary T cell influx triggered by both antiviral and anti‐HLA immunity. Biopsies with BK polyomavirus nephropathy contain a low percentage of T cells directed against viral and HLA antigens, but the majority of T cells appear to represent a secondary influx mediated by tissue injury.